2020
DOI: 10.3390/ijms21082804
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling of Normal and Malignant Human Colonic Stem Cells Identifies miRNA92a as a Regulator of the LRIG1 Stem Cell Gene

Abstract: MicroRNAs (miRNAs) have a critical role in regulating stem cells (SCs) during development, and because aberrant expression of miRNAs occurs in various cancers, our goal was to determine if dysregulation of miRNAs is involved in the SC origin of colorectal cancer (CRC). We previously reported that aldehyde dehydrogenase (ALDH) is a marker for normal and malignant human colonic SCs and tracks SC overpopulation during colon tumorigenesis. MicroRNA expression was studied in ALDH-positive SCs from normal and malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Indeed, an investigation of the literature shows that many miRNAs have been reported to target SC genes or genes involved in regulating SC properties ( Table S1 ). Moreover, using miRNA expression profiling of isolated normal and malignant human colonic SCs [ 138 , 139 ], we showed that miR-23b and miR-92a are regulators of the LGR5 and LRIG1 SC genes, respectively. Findings from these two published studies and from our review of TCGA study results are described further below.…”
Section: Mirnas Implicated In Development Of Crc Stem Cell Populatmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, an investigation of the literature shows that many miRNAs have been reported to target SC genes or genes involved in regulating SC properties ( Table S1 ). Moreover, using miRNA expression profiling of isolated normal and malignant human colonic SCs [ 138 , 139 ], we showed that miR-23b and miR-92a are regulators of the LGR5 and LRIG1 SC genes, respectively. Findings from these two published studies and from our review of TCGA study results are described further below.…”
Section: Mirnas Implicated In Development Of Crc Stem Cell Populatmentioning
confidence: 99%
“…We also took an independent approach to identify miRNAs in purified human colonic SCs [ 139 ], which was based on a more extensive screen involving miRNA expression profiling of ALDH+ SCs isolated from fresh normal colonic epithelium and CRC tissue. This was done to identify additional miRNAs involved in the SC origin of CRC.…”
Section: Mirnas Implicated In Development Of Crc Stem Cell Populatmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this context, the expression of four miRNAs has been found to be altered in CRC stem cells with respect to normal stem cells. In particular, the overexpression of miRNA92a appears to contribute to cancer stem cell origin [8].…”
mentioning
confidence: 99%